A Story to Tell': learning from the life-stories of older people with intellectual disabilities in Ireland. - Hamilton, Carol; Atkinson, Dorothy (Wiley Blackwell, 2009)
This article draws on life-stories told by older people with intellectual disabilities for a research study in the Republic of Ireland. Research participants recalled their experiences of confinement, coercion and exclusion that resulted from their being labelled as having intellectual disabilities. Participants also recalled the positive interactions with workers and family members that sustained them during these difficult times. Extracts from these narratives show how past medical and social processes interlinked to classify members of this group as 'deficient' or 'lacking' in some way. Life-stories collected in this project illustrate the value of a narrative approach to exploring how services might begin to enhance the quality of support currently provided to older people with intellectual disabilities. However, life-story work in a service setting is far from straightforward, and support is needed for staff involved in this process.
Keywords: Digital archives; institutional practices